2017
DOI: 10.1111/his.13265
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive characterization of RSPO fusions in colorectal traditional serrated adenomas

Abstract: The present study identified RSPO fusion transcripts, including three novel transcripts, in one-third of colorectal TSAs and showed that PTPRK-RSPO3 fusions were the predominant cause of RSPO overexpression in colorectal TSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 22 publications
6
32
0
Order By: Relevance
“…The present study identified RSPO fusions in 33 of 99 TSAs (33%), 29 of which had previously reported PTPRK – RSPO3 fusions. This is in agreement with previous studies demonstrating that PTPRK – RSPO3 is the predominant RSPO fusion in TSAs . In addition, we identified EIF3E – RSPO2 and PIEZO1 – RSPO2 fusions in three and one TSAs, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The present study identified RSPO fusions in 33 of 99 TSAs (33%), 29 of which had previously reported PTPRK – RSPO3 fusions. This is in agreement with previous studies demonstrating that PTPRK – RSPO3 is the predominant RSPO fusion in TSAs . In addition, we identified EIF3E – RSPO2 and PIEZO1 – RSPO2 fusions in three and one TSAs, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly to other serrated lesions, most TSAs harbour either KRAS or BRAF mutations, which lead to activation of the mitogen‐activated protein kinase pathway . In addition, our previous studies have shown that most TSAs also have genetic alterations in genes encoding WNT pathway components, including RNF43 , APC and CTNNB1 mutations, and RSPO fusions . These genetic alterations are found in a mutually exclusive manner, supporting their roles in the activation of the WNT pathway in TSAs.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations